Whole-body vibration training effects on the physical performance of basketball players - Colson, S. S.; Pensini, M.; Espinosa, J.; Garrandes, F.; Legros, P. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to investigate the influence of 4 weeks of whole-body vibration training added to the conventional training of basketball players. Eighteen competitive basketball players (13 [male sign], 5 [female sign], 18-24 years old) were randomly assigned to a whole-body vibration group (WBVG, n = 10; 7 [male sign] and 3 [female sign]) or a control group (CG, n = 8; 6 [male sign] and 2 [female sign]). During the 4-week period, all subjects maintained their conventional basketball training program. The members of WBVG were additionally trained 3 times a week for 20 minutes on a vibration platform (10 unloaded static lower limb exercises, 40-Hz, 4-mm, Silverplate(R)). Testing was performed before and after the 4-week period and comprised strength assessment, vertical jump performance, and a 10-m sprint test. The maximal voluntary isometric strength of the knee extensors significantly increased (p < 0.001) after vibration training, as did squat jump (SJ) height (p < 0.05), whereas performance of the countermovement jump, drop jump, 30-second rebound jump, and 10-m sprint remained unchanged. The results of the present study indicated that a 4-week whole-body vibration training program added to the conventional training of basketball players during the preseason is an effective short-term stimulus to enhance knee extensor strength and slightly SJ performance.